Ideologyas a factor of personal ethnic worldview transformation - Oleksander Ivaskevych (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This study determined the ethno-cultural dimensions of Ukrainians worldview that allows forecasting the dynamic changes in value systems and their connections with the ideological influence of various actors on Ukrainian political space. There havebeenmarkedthe high level of individuality, tolerance for uncertainty,contextuallity,masculinityandidentify specific distance of power, characterized by lack of trust in the political authorities and negative attitude to them. This accentuation may be associated with the constant threat of integrity of Ukraine as a state,which exists throughout the existence of Ukraine, and Ukrainian ethnic worldview and can be related to the crisis taking place in Ukraine.According to this study, it is possible to form thenational ideology and mechanisms of its implementation. The map of Ukrainian ethnic worldview that can explain the social processes taking place in Ukrainian society should be used in order to forecast the implementation influence of ideology.Dynamic and controversial events of the modern world is the result of the crisis of globalization and the revival of world ideologies that require finding a qualitatively new practical ways to solve them. In the current political psychology, along with the problems of political leadership, management, psychology of terrorism, motivation and formation of beliefs, making political decisions remain unresolved the issue of ideological support in socio-political life of various geopolitical dimensions.
Keywords: worldview; ideology; ethnopsychological dimensions